2019
DOI: 10.1111/1748-5967.12337
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and function of ovipositorial and tarsal sensilla of female Asian citrus psyllid

Abstract: The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama (Hemiptera:Psyllidae), is one of the most important pests of citrus plants worldwide, due to be the dominant vector of the devastating citrus disease Huanglongbing (HLB). Selection of suitable oviposition site is a crucial event of phytophagous insect life. Usually, the chemical and physical characteristics of a host plant were recognized by sensilla on the ovipositor and tarsi of a phytophagous insect after settling on a plant surface. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A recent study showed that there were a large number of sensilla on the ovipositor of female ACPs, including trichoid sensilla, which are related to chemical perception. When these sensilla were deactivated using HCl, an oviposition assay revealed the production of a significantly lower number of eggs than were produced by individuals that were treated with distilled water, and the results suggested that the ovipositor of the female ACP likely perceives odour to determine whether to lay eggs. Accordingly, in the ACP, DcitOBP6 is highly expressed in the ovipositor in addition to the antennae and mediates the recognition of β‐caryophyllene by females.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that there were a large number of sensilla on the ovipositor of female ACPs, including trichoid sensilla, which are related to chemical perception. When these sensilla were deactivated using HCl, an oviposition assay revealed the production of a significantly lower number of eggs than were produced by individuals that were treated with distilled water, and the results suggested that the ovipositor of the female ACP likely perceives odour to determine whether to lay eggs. Accordingly, in the ACP, DcitOBP6 is highly expressed in the ovipositor in addition to the antennae and mediates the recognition of β‐caryophyllene by females.…”
Section: Discussionmentioning
confidence: 99%
“…Discriminating between host and nonhost species progresses through a series of behaviors, which begin with locating a potentially suitable plant, settling and probing, ingesting plant sap, and ovipositing. These behavioral components are regulated by plant-associated cues detected and evaluated by different types of sense organs or sensilla associated with varying structures of insects ( Ullman and McLean, 1986 ; Soroker et al., 2004 ; Liang et al., 2013 ; Zhang et al., 2019 ). Most of these behavioral processes and different sensilla functions are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these behavioral processes and different sensilla functions are poorly understood. The initial component, locating the host from a distance, is likely governed by visual or olfactory cues detected by ocular organs and olfactory sensilla on the head and antennae ( Ullman and McLean, 1986 ; Soroker et al., 2004 ; Liang et al., 2013 ; Zhang et al., 2019 ). The importance of visual cues is shown by the attractiveness of specific colors to pear psyllids ( Adams et al., 1983 ; Krysan and Horton, 1991 ; Czarnobai De Jorge et al., 2022 ; Czarnobai De Jorge et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%